Implementation of ChatGPT to Improve Students' Critical Thinking Abilities - Harahap, Deby Sagita (Indonesian Journal of Education and Social Humanities, 2024)
The integration of artificial intelligence (AI) tools, such as ChatGPT, in educational settings has become a topic of increasing interest in recent years. One of the main benefits of using ChatGPT in education is its potential to improve students' critical thinking skills. Critical thinking is the ability to analyze and evaluate complex situations or problems, identify patterns and relationships, and make decisions based on logical reasoning. These skills are important for success in both academic and professional settings. However, research shows that many students have difficulty thinking critically. ChatGPT, developed by OpenAI, is a large language model that can generate human-like text based on the input it receives. It can answer questions, generate essays, summarize texts, and even engage in conversations. Using ChatGPT in the world of education can provide several benefits that help students develop their critical thinking skills.